Effect of hydroocolloid concentration on bioactive compounds, bioaccessibility and instrumental texture of guava (Psidium guajava L.) (Research, Society and Development, 2020)
The food industry looks for innovations that can favor the use and increase of the fruit pulp market. Gelling agents can be used in the development of novel food products with a wide variety of textures, such as structured fruits. The objective of this study was to develop structured guava bars using agar and gellan gum as gelling agents and evaluate the impact of these hydrocolloids on bioactive compounds and antioxidant activity, before and after gastrointestinal in vitro digestion, as well as evaluate the texture profile of the structure guava bars. Formulations were prepared with agar and gellan gum hydrocolloids at concentrations of 0.25, 0.50, 0.75 and 1% (w / w). Ascorbic acid content determined by  titration method, Total Phenolic Content (TPC) assessed by Folin-Ciocalteu reagent and antioxidant capacity performed using  ABTS method were evaluated before and after in vitro digestion. In vitro bioaccessibility was performed with pepsin solubilized in 0.1 mol L-1 HCl during gastric phase and bile-pancreatin salts, solubilized with 0.1 mol L-1 NaHCO3 in intestinal phase. The values of hardness and adhesiveness increased as the concentration of hydrocolloids increased. In addition, these hydrocolloids, mainly gellan gum, provided high values of bioaccessibility of vitamin C, polyphenols and antioxidant activity. Therefore, structured guavas bars have chemical characteristics similar to in natura guava pulp. Moreover, the results indicated that the types and concentration of hydrocolloid had a direct influence on the bioaccessibility of the studied samples.